CAREC road safety engineering manual 1 road safety audit. (Metro Manila, Philippines Asian Development Bank, 2018)
Research indicates that up to 28% of crashes are due to the road environment. The first and most important objective of road safety audit is to minimize the risk of crashes, and to minimize the severity of any crashes that may occur on a new road project. Road safety audit is suggested to be undertaken for all CAREC road projects. This manual provides full information for those who undertake the audits (practitioners) as well as for those who manage the audit process (policy makers).
Keywords: Central Asia -- Economic integration; Central Asia cooperation -- Economic aspects; International economic relations; Electronic books